Biometrical analysis of bovine female reproductive system (Bangladesh Journal of Livestock Research, 2020)
This study was conducted to investigate basic biometric information on organs of female reproductive system of indigenous cows. Ovaries were grouped on the basis of corpus luteum (CL) and ovarian position in the tract. Visible follicles were counted and graded as small (8.0mm). Oocytes were recovered from all visible follicles and graded into four groups (grade 1 to 4). Results showed that the oviduct, horn, body of the uterus and cervix of cow’s reproductive system were longer and wider than heifers, respectively. Except length, the width and visible follicle numbers in the ovary did not vary with ovarian position or CL. Weight of left and right ovaries did not differ. Weight of ovary was increased (P>0.01) in presence of CL. Each ovary possessed 9.65±5.91visible follicles belonging to small (5.38±0.37), medium (3.57±0.23) and large (0.72±0.07) groups. Oocyte recovery rate was 62.16±1.46%. Among the recovered oocytes 52.01±1.63% were belonging to grade 1 and 2. This study provides baseline on biometry of female reproductive system along with follicular statistics of indigenous cows.Bangladesh J. of Livestock Res. 20(1-2): 1-7, Jan-Dec 2013